Simultaneous Anterior and Posterior Surgery in the Management of Tuberculous Spondylitis with Psoas Abscess in Patients with Neurological Deficits - Suh, Kuen Tak (Korean Society of Spine Surgery, 2008)
STUDY DESIGN: This is a retrospective study. PURPOSE: We wanted to evaluate the treatment outcomes of performing simultaneous anterior and posterior surgery for patients with tuberculous spondylitis and psoas abscess. OVERVIEW OF LITERATURE: Although various treatment options have been used for spinal tuberculosis, there are only a few reports on the treatment of tuberculous spondylitis with psoas abscess. METHODS: Between March 1997 and February 2006, we performed operations on 14 cases of tuberculous spondylitis with psoas abscess. All the cases underwent anterior debridement with an interbody bone graft and posterior fusion with using pedicle screws. RESULTS: Under the Frankel classification, 1 case improved by two grades, 10 cases improved by 1 grade and 3 cases demonstrated no change. The Kirkaldy-Willis functional outcomes were classified as excellent in 10 cases and good in 4. One year after surgery, bony union was confirmed in all 14 cases. The mean kyphotic angle of the spinal lesion was 12.4° and the mean lordotic angle at the final follow-up was 6.4°. Postoperative complications (superficial wound infections) were encountered in 2 cases. CONCLUSIONS: Our results demonstrate that anterior debridement with interbody bone grafting and posterior instrumented fusion can provide satisfactory results for treating tuberculous spondylitis with psoas abscess in patients with neurological deficits.